The Overdose Crisis and Using Alone: Perspectives of People Who Use Drugs in Rural and Semi-Urban Areas of British Columbia. (15th October 2022) - Fernando, Saranee; Hawkins, Jennifer; Kniseley, Marinel; Sikora, Mike; Robson, James; Snyder, Daniel; Battle, Chris; Salmon, Amy
Abstract: Background: A significant rise in the rate of overdose deaths in British Columbia (BC), driven by fentanyl contamination of the illicit drug supply, led to the declaration of a public health emergency in 2016. Those at greatest risk of death are people who use alone. This community-based participatory action research study based in the Fraser East region of BC study aimed to overview underlying factors that contribute to unwitnessed overdoses in semi-urban and rural settings. Methods : This descriptive study used a community-based participatory action research model with peer research associates (PRAs) involved at various research stages. In total, 22 interviews were conducted with participants aged 19 and over who used illicit drugs in the Fraser East since the start of the public health emergency in 2016. A collaborative data analysis approach was taken for data interpretation, and content analysis was performed to explore themes surrounding using alone. Results : Among people who use drugs (PWUD), using alone was found to be influenced by (a) the availability of drugs and personal funds, (b) personal safety, (c) stigma and shame, (d) protecting privacy, (e) mental health conditions and addiction, and (f) the lack of engagement with harm reduction services. At times, using alone was due to unforeseen, episode-specific situations. Conclusion : A multi-dimentional and context-specific approach is needed in overdose prevention and response for people who use drugs alone. There is need for enhanced approaches that address or include support services for families to reduce stigma and isolation of those at risk of an overdose.